Host-Bacteria Crosstalk at the Dentogingival Junction - M. T. Pöllänen; M. A. Laine; R. Ihalin; V.-J. Uitto (International Journal of Dentistry)
The dentogingival junction is of crucial importance in periodontal host defense both structurally and functionally. Oral bacteria exert a constant challenge to the host cells and tissues at the dentogingival junction. The host response is set up to eliminate the pathogens by the innate and adaptive defense mechanisms. In health, the commensal bacteria and the host defense mechanisms are in a dynamic steady state. During periodontal disease progression, the dental bacterial plaque, junctional epithelium (JE), inflammatory cells, connective tissue, and bone all go through a series of changes. The tissue homeostasis is turned into tissue destruction and progression of periodontitis. The classical study of Slots showed that in the bacterial plaque, the most remarkable change is the shift from gram-positive aerobic and facultatively anaerobic flora to a predominantly gram-negative and anaerobic flora. This has been later confirmed by several other studies. Furthermore, not only the shift of the bacterial flora to a more pathogenic one, but also bacterial growth as a biofilm on the tooth surface, allows the bacteria to communicate with each other and exert their virulence aimed at favoring their growth. This paper focuses on host-bacteria crosstalk at the dentogingival junction and the models studying it in vitro.